Strength Model of Backfill-Rock Irregular Interface Based on Fractal Theory - Zhang, Yue; Zhang, Zhihong; Guo, Lijie; Du, Xiuli (Frontiers in Materials, 2021)
In the two-step open stope subsequent filling mining method, the determination of the strength model for the backfill-rock interface is of great engineering significance to study the stress distribution and stability of the backfill in the stope. Considering the deformation mechanism of the interface and the interaction of the asperities, a strength model for backfill-rock with irregular interface has been proposed based on fractal theory, which can effectively describe the shear mechanical behavior of interfaces with random roughness. The model has been compared with the two-body mechanistic model and good agreements have been achieved. The results show that the shear strength of the interface changes non-linearly with increasing fractal dimension D, when the fractal dimension D is in the range of 1~1.12. The complete relationship between the interface shear strength and the fractal dimension is given, as the fractal dimension increases from 1 to 2 based on the presented model. At the same time, the quantitative relationship between the interface and backfill friction angles during direct shear testing is analyzed.